Customer Decision to Visit Agrotourism Farms in Kalimantan Barat - Dolorosa, Eva; Suharyani, Anita; Sawerah, Siti; Kurniati, Dewi (Jurnal Social Economic of Agriculture, 2025)
The agriculture and tourism sectors are the country's major economic contributors. The growing intersection between agriculture and tourism presents a unique opportunity to enhance rural development and sustainability. Traditional farming is facing numerous challenges. These include fluctuating market prices, climate change and the pressures of urbanization. In this context, it is clear that agrotourism offers farmers a way to diversify their income stream and increase their resilience. This study provides a comprehensive analysis of the consumer decision-making and the factors that influence consumers to visit agrotourism. This study aims to describe the characteristics of agrotourism consumers and analyze the factors that influence customers' decisions to visit agrotourism farms. We surveyed 182 respondents in Kubu Raya, Sintang, and Singkawang City. The results showed a number of factors formed from several variables that influence consumer decisions to visit agritourism, namely Social, internal, psychological and motivation factors.